Stain-resistant PCR ABS laser etching material and preparation method thereof
By constructing an anti-fouling surface layer using modified organosilicon micropowder and ultra-high molecular weight polyethylene powder, an anti-fouling PCR ABS laser engraving material is developed, solving the problem of easy contamination of ordinary laser engraving materials. This material improves the clarity and environmental friendliness of key characters, is compatible with various resin substrates, and reduces production costs and environmental pressure.
Patent Information
- Application Number
- CN202512051230.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-03-17
AI Technical Summary
Existing ordinary laser engraving materials are easily contaminated by sweat, alcohol and other stains on consumer electronics products such as computer keyboards, resulting in blurred characters, affecting the user experience and brand image. In addition, traditional screen printing processes have problems such as ink peeling and environmental pollution.
Using anti-fouling PCR ABS laser engraving material, a hydrophobic and anti-fouling surface layer is constructed by modifying organosilicon micro powder and modified ultra-high molecular weight polyethylene powder. Combined with inorganic powder modification and resin synthesis, a wear-resistant and self-lubricating laser engraving material is formed, avoiding the need for additional coating treatment.
The material itself is stain-resistant and durable, extends the clarity of key characters, reduces cleaning frequency, simplifies the production process, is compatible with a variety of resin substrates, reduces development costs, responds to environmental protection policies, and improves production efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of PCR ABS material modification and laser engraving function integration, in particular to an anti-fouling PCR ABS laser engraving material and a preparation method thereof. BACKGROUND
[0002] In the field of computer keyboard production, with the improvement of environmental protection requirements and the increase of processing efficiency requirements, the character manufacturing process has gradually shifted from traditional silk screen printing process to laser engraving process. Compared with the silk screen printing process which needs to rely on solvent-containing ink, has the risk of ink falling off and pollutes the environment with waste gas and waste liquid, the laser engraving process has the advantages of high processing efficiency, high pattern precision, no solvent emission, etc., and can also realize diversified color engraving requirements such as black engraving white, white engraving black, gray engraving white and color laser engraving, which is suitable for different product appearance design scenes; effectively meets the development trend of green production and fine manufacturing of consumer electronic products, and has been widely used in various computer keyboard key character processing. In addition, for foreign small language keyboard production scenes, the silk screen printing process needs to open a new mold for different language characters, which not only increases the development cost and prolongs the delivery cycle, but also has the risk of mold idling waste. The laser engraving process only needs to adjust the parameter settings on the computer to realize the engraving of different language characters, which significantly improves the production flexibility and adaptation efficiency of small language keyboards.
[0003] However, with the increasing requirements of consumers on product use experience and durability, the defects of existing ordinary laser engraving materials gradually become prominent: the laser engraved characters are easily attached and penetrated by common dirt such as hand sweat, alcohol, hand cream and lipstick in daily use, causing the characters to gradually discolor and blur. According to industry research data, the keyboard keys using ordinary laser engraving materials have obvious dirt and reduced recognition within 1-3 months under normal use conditions; in summer high temperature and high humidity environment or in tropical regions such as Southeast Asia, the environmental humidity is large, and the dirt problem is more serious. The white characters of some keys become completely black within 1 month of use, which not only affects the user's recognition and operation of the key function, but also damages the brand image due to the deterioration of the product appearance, which becomes a key bottleneck restricting the further popularization and application of laser engraving process in the field of keyboards. SUMMARY
[0004] In view of the deficiencies of the prior art, the present application provides an anti-fouling PCR ABS laser engraving material and a preparation method thereof, which solves the defects of character falling off and environmental pollution when consumer electronic products use silk screen printing process, and the problem of surface laser engraved characters / patterns being easily contaminated by hand sweat, alcohol and daily dirt and becoming black in the application of ordinary laser engraving materials in consumer electronic products such as keyboard keycaps.
[0005] To achieve the above purpose, the technical scheme is as follows: The anti-fouling type PCR ABS laser engraving material comprises the following raw materials in parts by weight: 50-90 parts of PCR ABS resin, 6-10 parts of modified silicone micro powder, 2-15 parts of modified ultra-high molecular weight polyethylene powder, 2-8 parts of azodicarbonamide, 2-6 parts of methyl methacrylate-butyl acrylate copolymer, 1-3 parts of antioxidant 1010, 0.5-2.5 parts of glass microbeads, 0.5-2 parts of anatase titanium dioxide, 0.2-1 part of silane coupling agent KH-550, 0.5-1.0 parts of calcium-zinc stabilizer, 0.1-0.5 parts of carbon black, 0.05-0.1 parts of polyethylene wax, and 0.4-1 parts of anhydrous ethanol.
[0006] Further, the modified silicone micro powder is prepared according to the following steps: A1, the methylphenyl silicone micro powder with a particle size of 50 μm is placed in a plasma treatment instrument, the power is set to 120 W, the nitrogen atmosphere is 0.06 MPa, and the treatment time is 18-25 min; the silane coupling agent KH-570, anhydrous ethanol and deionized water are mixed in proportion, the pH is adjusted to 5 with dilute acetic acid, stearic acid is added and stirred to dissolve, a modified liquid is prepared, and the modified liquid is transferred into a mixing kettle and deoxygenated by nitrogen for 30 min; the plasma-activated silicone micro powder is added into the mixing kettle, and the stirring reaction is carried out at 45-55 DEG C and a rotating speed of 550 r / min for 2.5-3.5 h, during which nitrogen is introduced every 1 h for 10 min to isolate oxygen; after the reaction is completed, the product is filtered, washed twice with anhydrous ethanol and once with deionized water, and dried at 85-95 DEG C for 5 h to obtain the first modified silicone micro powder; The whole process is protected by nitrogen to avoid oxidation of the powder, and the residual impurities can be removed through multi-step washing and precise temperature drying to ensure the purity and activity of the first modified powder.
[0007] A2, the microcrystalline wax is heated and melted, deionized water and sodium dodecyl sulfate are added, and the microcrystalline wax emulsion is prepared by emulsifying at 55 DEG C water bath under the condition of high-speed stirring at 6000-7000 r / min for 30 min; the polyether modified silicone oil is added into the emulsion, and the composite coating liquid is formed by ultrasonic dispersion at 150 W for 1 h; the first modified silicone micro powder is added into the composite coating liquid, and the stirring is carried out in a 55 DEG C constant temperature water bath at a rotating speed of 350-450 r / min for 2-2.5 h, during which ultrasonic is introduced every 30 min for 10 min; after the reaction, the product is centrifuged and washed with deionized water for 3 times, and dried at 95-100 DEG C for 6 h to obtain the second modified silicone micro powder; The stable microcrystalline wax emulsion can be prepared by 55 DEG C water bath emulsification combined with high-speed stirring, and the uniform composite coating liquid can be formed by ultrasonic dispersion of the polyether modified silicone oil; the uniform coating of the powder by the coating liquid can be realized by low-speed stirring combined with intermittent ultrasonic; the coating structure can be solidified by multiple water washing and high-temperature drying to ensure the anti-fouling stability of the second modified powder.
[0008] A3. Take 15nm nano-silica and polyethylene glycol 6000 and add them to anhydrous ethanol. Disperse them by ultrasonication at 150W for 1h. Then add styrene-butadiene rubber powder and dicumyl peroxide and stir until a uniform suspension system is formed. Add the second modified organosilicon micro powder to the suspension system and stir at 300-400r / min for 2.5-3.5h under nitrogen protection at 65-75℃. After cooling to room temperature, centrifuge, wash twice with anhydrous ethanol, dry at 100-110℃ for 7h and pass through a 200-mesh sieve to obtain modified organosilicon micro powder.
[0009] Medium-temperature stirring under nitrogen protection can promote the full progress of the grafting reaction. Multi-stage washing, high-temperature drying and sieving can enhance the wear resistance and self-lubricating properties of the powder, ultimately achieving synergistic optimization of anti-fouling durability and laser engraving compatibility.
[0010] Furthermore, the modified ultra-high molecular weight polyethylene powder is prepared using the following specific steps: B1. Take ultra-high molecular weight polyethylene powder, dicumyl peroxide, and antioxidant DSTDP, blend them, and add them to a twin-screw extruder. The barrel temperature gradient is: zone 1 150℃, zone 2 165℃, zone 3 170℃, and die head 168℃. The screw speed is 250 r / min, and the feeding speed is 8 kg / h. The extruded strip is cooled to room temperature with water and pulverized into powder with a particle size of 60 μm. Take the pretreated powder and add it to a mixer. Set the temperature to 135℃ and the speed to 60 r / min. After the material softens, add maleic anhydride monomer and benzoyl peroxide, and continue the mixing reaction for 2 hours. During this period, increase the speed to 100 r / min for 1 minute every 20 minutes. After the reaction is completed, take out the material, cool it to room temperature, pulverize it, and extract it with acetone Soxhlet for 8 hours. The extracted material is dried at 80℃ for 5 hours to obtain the first modified ultra-high molecular weight polyethylene powder. Gradient temperature extrusion and 60μm particle size control ensure uniform pretreatment of ultra-high molecular weight polyethylene powder; 135℃ intensive mixing provides a suitable temperature for maleic anhydride grafting; intermittent high-speed stirring can enhance material shear mixing, promote full grafting of polar groups, improve compatibility with subsequent modified components, and optimize the material interface bonding force.
[0011] B2. Add nano zinc oxide, polyethylene glycol 4000, and sodium dodecylbenzene sulfonate to deionized water and ultrasonically disperse at 150W for 1 hour. Add baking soda and citric acid to the dispersion and stir for 10 minutes. Add the first modified ultra-high molecular weight polyethylene powder to the dispersion, transfer to a 50℃ constant temperature water bath, stir at 400r / min for 2 hours, and ultrasonicate for 10 minutes every 30 minutes. Then add silane coupling agent KH-550, adjust the pH to 5.5 with dilute hydrochloric acid, and continue stirring for 1.5 hours. After the reaction is complete, filter to separate the material, wash with deionized water 3 times, and dry at 100℃ for 6 hours to obtain the second modified ultra-high molecular weight polyethylene powder. A 50℃ water bath combined with 400r / min stirring and intermittent ultrasound can promote the full interaction between the powder and the dispersion; adjusting the pH to 5.5 creates a suitable environment for the coupling agent reaction and improves the compatibility between the powder and the substrate.
[0012] B3. Take the second modified ultra-high molecular weight polyethylene powder and add it to a three-necked flask containing toluene. Purge with nitrogen at a flow rate of 50 ml / min for 30 min, heat to 80℃, and stir at 300 r / min for 30 min. Add the recovered liquid silica gel and polyurethane prepolymer, stir for 10 min, then add dibutyltin dilaurate. Stir and react for 3 h under nitrogen protection. Add ethanolamine and continue the reaction for 1 h. After the reaction is completed, cool to room temperature, centrifuge the material, wash the precipitate twice with toluene and once with anhydrous ethanol, and dry at 110℃ for 7 h to obtain modified ultra-high molecular weight polyethylene powder.
[0013] A composite coating layer can be constructed by stepwise reaction of recycled liquid silicone and polyurethane prepolymer; washing with toluene and anhydrous ethanol can remove residual impurities, and drying at 110℃ ensures the dryness of the powder, optimizes the powder's lubricity and anti-fouling durability, and at the same time realizes the reuse of recycled materials, thus improving environmental protection.
[0014] Furthermore, the recycled liquid silica gel used in the modified ultra-high molecular weight polyethylene powder undergoes pretreatment. Specifically, the recycled liquid silica gel is pulverized and filtered through a 100-mesh filter to remove impurities, thus avoiding affecting the purity of the material. It is then placed in a vacuum degassing machine and degassed at 120°C and -0.095MPa for 2 hours to remove internal air bubbles, prevent powder structure defects caused by air bubbles during the modification process, and ensure the performance stability of the modified ultra-high molecular weight polyethylene powder.
[0015] Furthermore, the ratio of methylphenyl organosilicon micro powder, silane coupling agent KH-570, anhydrous ethanol, deionized water, and stearic acid in A1 is 100g: 25-35ml: 90-110ml: 6-10ml: 0.2-0.3g.
[0016] Furthermore, the ratio of microcrystalline wax, deionized water, sodium dodecyl sulfate, polyether-modified silicone oil, and first-modified organosilicon micropowder in A2 is 10-15g: 90-120ml: 0.2-0.4g: 2-4g: 100g.
[0017] Furthermore, the ratio of nano-silica, polyethylene glycol 6000, anhydrous ethanol, styrene-butadiene rubber powder, dicumyl peroxide, and second-modified organosilicon micro powder in A3 is 6-10g: 1.5-2.5g: 70-90ml: 2-3.5g: 0.3-0.5g: 100g.
[0018] Furthermore, in B1, the ratio of ultra-high molecular weight polyethylene powder, dicumyl peroxide, and antioxidant DSTDP is 100g: 2.5-3.5g: 0.1-0.2g; the ratio of pretreated powder, maleic anhydride monomer, and benzoyl peroxide is 100g: 6.5-7.5g: 0.3-0.4g.
[0019] Furthermore, the ratio of nano zinc oxide, polyethylene glycol 4000, sodium dodecylbenzenesulfonate, deionized water, baking soda, citric acid, first-modified ultra-high molecular weight polyethylene powder, and silane coupling agent KH-550 in B2 is 10g:2g:0.1g:100ml:0.4-0.6g:0.1-0.2g:100g:5-7ml.
[0020] Furthermore, the ratio of the second modified ultra-high molecular weight polyethylene powder, toluene, recycled liquid silica gel, polyurethane prepolymer, dibutyltin dilaurate, and ethanolamine in B3 is 100g:150ml:10-12g:8-10g:0.2-0.4g:5-6g; wherein the polyurethane prepolymer is aromatic, with an NCO content of 6.5% and a number average molecular weight of 1000-1500.
[0021] Furthermore, the modified organosilicon micropowder undergoes a three-stage modification process to synergistically enhance the material's antifouling properties and compatibility. The first modification employs plasma treatment combined with a composite modification liquid of silane coupling agent KH-570 and stearic acid to activate active sites on the powder surface and graft polar groups, thereby improving the interfacial bonding force with PCR ABS resin. The second modification involves a microcrystalline wax-polyether modified silicone oil composite coating to construct a low surface energy hydrophobic layer, endowing the powder with basic antifouling capabilities. The third modification utilizes nano-silica and styrene-butadiene rubber powder grafting to form a micro-nano rough structure, constructing a micro-nano rough hydrophobic structure to enhance hydrophobic and antifouling performance, while simultaneously improving the powder's wear resistance and self-lubricating properties, optimizing the overall antifouling durability and laser engraving compatibility of the material.
[0022] Furthermore, in the three-stage modification process of the modified ultra-high molecular weight polyethylene powder, the first modification introduces polar groups through maleic anhydride grafting reaction; the second modification involves nano zinc oxide adsorbing and depositing on the powder surface through electrostatic interaction and hydrogen bonding, forming a micro-nano rough structure, which, together with low surface energy components, achieves hydrophobicity and antifouling; and the third modification constructs a surface structure that combines lubricity and antifouling through composite coating of recycled liquid silica gel and polyurethane prepolymer.
[0023] The preparation method of anti-fouling PCR ABS laser-engraved material includes the following steps: S1. Place all solid raw materials into a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.09MPa, and dry for 6 hours; take 0.1-0.5 parts of carbon black, add 0.05-0.1 parts of polyethylene wax and 0.4-1 parts of anhydrous ethanol, put them into a small grinder, grind and disperse to break up carbon black agglomerates, so that the particle size distribution D90≤5μm, and make a uniform pigment paste to ensure that it is uniformly dispersed in the material, and ensure that the laser engraving pattern is clear and free of broken line defects; S2. Add 0.5-2.5 parts of glass microspheres, 0.5-2 parts of anatase titanium dioxide, and 6-10 parts of modified organosilicon powder to a high-speed homogenization tank. Set the speed to 500 r / min and stir at room temperature for 5 min. Then spray 0.2-1 parts of silane coupling agent KH-550 and continue stirring for 10 min. Stirring at 500 r / min in conjunction with the coupling agent spraying can achieve surface modification of inorganic powders. Reduce the speed to 300 r / min to avoid powder splashing. Add 50-90 parts of PCR ABS resin and 2-15 parts of modified ultra-high molecular weight polyethylene powder. After all the powder is added, slowly increase the speed to 800 r / min and stir for 15 min to ensure uniform dispersion of the substrate and modified powder, reduce component separation, and improve the uniformity of material properties. S3. While maintaining the stirring speed, add 2-8 parts of azodicarbonamide, 2-6 parts of methyl methacrylate-butyl acrylate copolymer, 1-3 parts of antioxidant 1010, and 0.5-1.0 parts of calcium-zinc stabilizer in sequence, with a 3-minute interval between each addition. Stir for 25 minutes until no visible lumps are visible. Spray the prepared pigment paste evenly into the mixture, set the stirring speed to 800 r / min, and simultaneously perform ultrasonic dispersion at 200W and 20kHz, sonicating for 5 minutes every 15 minutes, and continuing to stir for 80 minutes. The combination of stirring and intermittent ultrasonication can promote the uniform dispersion of the pigment paste, prevent uneven laser engraving effect caused by carbon black agglomeration, and ensure the synergistic effect of various functional additives, optimizing the material's anti-fouling and laser engraving performance. S4. Feed the mixture into a twin-screw extruder and set the temperature as follows: feeding section 175℃, compression section 195℃, melting section 202℃, die head section 208℃, screw speed 350rpm, and feeding speed 22kg / h. After the material strip is slowly cooled in a 45℃ warm water bath and shaped in a 20℃ cold water bath, it is pelletized to obtain anti-fouling PCR ABS laser-engraved masterbatch.
[0024] This invention provides a stain-resistant PCR ABS laser-engraved material and its preparation method, which has the following beneficial effects: 1. Addressing the shortcomings of existing computer keypads made with ordinary laser engraving materials, where the laser-engraved characters are easily contaminated by hand sweat, alcohol, and everyday stains, becoming blurred and less legible after 1-3 months of use, this invention optimizes the formulation and process of synthetic resins. For example, modified organosilicon micropowder and modified ultra-high molecular weight polyethylene powder synergistically construct a hydrophobic and stain-resistant surface layer, blocking the adhesion and penetration of pollutants at the material level. Testing shows that even after immersion in synthetic sweat, contact with alcohol, and contamination from lipstick / carbonated beverages, the laser-engraved characters remain sharp, clear, and free of residual dirt, effectively extending the lifespan of the clear keypad characters and preventing a decline in product user experience and damage to brand image due to character contamination.
[0025] 2. Existing anti-fouling laser engraving materials are often limited by specific substrates, making it difficult to be compatible with the diverse resin requirements in the production of computer keyboards and calculator keys. However, the resin synthesis method used in this invention has broad applicability, covering most commonly used basic resins for keys, such as ABS, PS, PMMA, PC, PC / ABS alloy, PA, PBT, and POM. There is no need to adjust the core process framework separately for different resins; only minor parameter adjustments based on substrate characteristics are required to achieve both anti-fouling and laser engraving functions. Furthermore, for the production needs of keyboards for less common languages, no additional molds are required; different language characters can be quickly adapted simply by adjusting laser engraving parameters via computer, significantly reducing development costs, shortening delivery cycles, and improving the flexibility of large-scale production of keyboards for less common languages. It also supports diverse color engraving modes such as black engraving on white, white engraving on black, gray engraving on white, and color laser engraving, meeting the appearance design requirements of different products without additional material formula adjustments, further expanding application scenarios. This feature lowers the technical threshold and cost of producing buttons with different materials, languages, and colors, providing more flexibility for material selection, global adaptation, and appearance innovation for products such as keyboards and calculators, and adapting to the needs of large-scale, multi-category production.
[0026] 3. Existing technologies often require an additional coating after laser engraving to improve the stain resistance of key characters. This not only increases production steps and costs but also may lead to secondary problems due to coating peeling. Traditional keys without stain resistance design rely on frequent cleaning and maintenance. This invention integrates stain resistance and laser engraving functions into the synthetic resin itself, eliminating the need for additional coatings or post-processing. This reduces VOC emissions and environmental pressure from coating processes, saves unnecessary processing steps, and improves production efficiency. Simultaneously, the material's inherent stain resistance reduces the frequency of key cleaning, further optimizing the overall user experience throughout the product's lifecycle, balancing environmental friendliness, economy, and practicality.
[0027] 4. The core substrate of this invention uses PCR (post-consumer recycled) material. The material itself has already achieved carbon emission reduction through resource recycling. Furthermore, the material is endowed with self-lubricating function through the synergistic modification of modified organosilicon micro powder and modified ultra-high molecular weight polyethylene powder. It does not need to rely on an external lubrication system. While reducing resource consumption, it further reduces the carbon footprint, responds to the "dual carbon" policy to a greater extent, and fits the industry trend of green manufacturing and sustainable development.
[0028] 5. In traditional keyboard manufacturing, the lubricating oil required for the oiling process is easily affected by external factors such as the overseas supply chain and environmental humidity / temperature, resulting in unstable key lubrication and high product defect rates, becoming a major pain point restricting production efficiency. This invention, through the self-lubricating properties of the material itself, eliminates the need for an additional oiling process, fundamentally avoiding the production risks associated with lubricant dependence, significantly reducing defect rates, simplifying the production process, and improving production capacity stability, providing an effective solution for cost reduction and efficiency improvement in the industry. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: S1. Place all solid raw materials into a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.09MPa, and dry for 6 hours; take 0.1 parts of carbon black, add 0.05 parts of polyethylene wax and 0.4 parts of anhydrous ethanol, put them into a small grinder, grind and disperse to break up the carbon black agglomerates, so that the particle size distribution D90≤5μm, and make a uniform pigment paste. S2. Add 0.5 parts glass microspheres, 0.5 parts anatase titanium dioxide, and 6 parts modified organosilicon powder to a high-speed homogenization tank. Set the speed to 500 r / min and stir at room temperature for 5 min. Then spray 0.2 parts silane coupling agent KH-550 and continue stirring for 10 min. Reduce the speed to 300 r / min, add 50 parts PCR ABS resin and 2 parts modified ultra-high molecular weight polyethylene powder. After all the powder is added, slowly increase the speed to 800 r / min and stir for 15 min. S3. While maintaining the stirring speed, add 2 parts azodicarbonamide, 2 parts methyl methacrylate-butyl acrylate copolymer, 1 part antioxidant 1010, and 0.5 parts calcium-zinc stabilizer in sequence, with a 3-minute interval between each addition. Stir for 25 minutes until no visible lumps are observed. Spray the prepared pigment paste evenly into the mixture, set the stirring speed to 800 r / min, and simultaneously perform ultrasonic dispersion at 200W and 20kHz, sonicating for 5 minutes every 15 minutes, and continuing to stir for 80 minutes. S4. Feed the mixture into a twin-screw extruder and set the temperature as follows: feeding section 175℃, compression section 195℃, melting section 202℃, die head section 208℃, screw speed 350rpm, and feeding speed 22kg / h. After the material strip is slowly cooled in a 45℃ warm water bath and shaped in a 20℃ cold water bath, it is pelletized to obtain anti-fouling PCR ABS laser-engraved masterbatch.
[0031] Example 2: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: S1. Place all solid raw materials into a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.09MPa, and dry for 6 hours; take 0.5 parts of carbon black, add 0.1 parts of polyethylene wax and 1 part of anhydrous ethanol, put them into a small grinder, grind and disperse to break up the carbon black agglomerates, so that the particle size distribution D90≤5μm, and make a uniform pigment paste. S2. Add 2.5 parts glass microspheres, 2 parts anatase titanium dioxide, and 10 parts modified organosilicon powder to a high-speed homogenization tank. Set the speed to 500 r / min and stir at room temperature for 5 min. Then spray 1 part silane coupling agent KH-550 and continue stirring for 10 min. Reduce the speed to 300 r / min and add 90 parts PCR ABS resin and 15 parts modified ultra-high molecular weight polyethylene powder. After all the ingredients are added, slowly increase the speed to 800 r / min and stir for 15 min. S3. While maintaining the stirring speed, add 8 parts of azodicarbonamide, 6 parts of methyl methacrylate-butyl acrylate copolymer, 3 parts of antioxidant 1010, and 1.0 part of calcium-zinc stabilizer in sequence, with a 3-minute interval between each addition. Stir for 25 minutes until no visible lumps are visible. Spray the prepared pigment paste evenly into the mixture, set the stirring speed to 800 r / min, and simultaneously perform ultrasonic dispersion at 200W and 20kHz, sonicating for 5 minutes every 15 minutes, and continuing to stir for 80 minutes. S4. Feed the mixture into a twin-screw extruder and set the temperature as follows: feeding section 175℃, compression section 195℃, melting section 202℃, die head section 208℃, screw speed 350rpm, and feeding speed 22kg / h. After the material strip is slowly cooled in a 45℃ warm water bath and shaped in a 20℃ cold water bath, it is pelletized to obtain anti-fouling PCR ABS laser-engraved masterbatch.
[0032] Example 3: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: S1. Place all solid raw materials into a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.09MPa, and dry for 6 hours; take 0.3 parts of carbon black, add 0.07 parts of polyethylene wax and 0.7 parts of anhydrous ethanol, put them into a small grinder, grind and disperse to break up the carbon black agglomerates, so that the particle size distribution D90≤5μm, and make a uniform pigment paste. S2. Add 1.5 parts glass microspheres, 1 part anatase titanium dioxide, and 8 parts modified organosilicon powder to a high-speed homogenization tank. Set the speed to 500 r / min and stir at room temperature for 5 min. Then spray 0.5 parts silane coupling agent KH-550 and continue stirring for 10 min. Reduce the speed to 300 r / min and add 70 parts PCR ABS resin and 8 parts modified ultra-high molecular weight polyethylene powder. After all the ingredients are added, slowly increase the speed to 800 r / min and stir for 15 min. S3. While maintaining the stirring speed, add 5 parts azodicarbonamide, 3 parts methyl methacrylate-butyl acrylate copolymer, 2 parts antioxidant 1010, and 0.7 parts calcium-zinc stabilizer in sequence, with a 3-minute interval between each addition. Stir for 25 minutes until no visible lumps are observed. Spray the prepared pigment paste evenly into the mixture, set the stirring speed to 800 r / min, and simultaneously perform ultrasonic dispersion at 200 W and 20 kHz, sonicating for 5 minutes every 15 minutes, and continuing to stir for 80 minutes. S4. Feed the mixture into a twin-screw extruder and set the temperature as follows: feeding section 175℃, compression section 195℃, melting section 202℃, die head section 208℃, screw speed 350rpm, and feeding speed 22kg / h. After the material strip is slowly cooled in a 45℃ warm water bath and shaped in a 20℃ cold water bath, it is pelletized to obtain anti-fouling PCR ABS laser-engraved masterbatch.
[0033] Example 4: Preparation of modified organosilicon micropowder. The specific preparation steps are as follows: A1. Take 100g of methylphenyl organosilicon micropowder with a particle size of 50μm, put it into a plasma treatment instrument, set the power to 120W, nitrogen atmosphere to 0.06MPa, and treat for 18min; mix 25ml of silane coupling agent KH-570, 90ml of anhydrous ethanol and 6ml of deionized water, adjust the pH to 5 with dilute acetic acid, add 0.2g of stearic acid and stir to dissolve, to prepare a modified solution, transfer it to a mixing vessel, and purge with nitrogen for 30min to remove oxygen; add the plasma-activated organosilicon micropowder to the mixing vessel, stir and react at 45℃ and 550r / min for 2.5h, during which nitrogen is purged for 10min every 1h to isolate oxygen; after the reaction is completed, filter, wash twice with anhydrous ethanol and once with deionized water, and dry at 85℃ for 5h to obtain the first modified organosilicon micropowder; A2. Take 10g of microcrystalline wax, heat and melt it, add 90ml of deionized water and 0.2g of sodium dodecyl sulfate, and emulsify it at 6000r / min for 30min under the condition of keeping it in a 55℃ water bath to obtain a microcrystalline wax emulsion; add 2g of polyether modified silicone oil to the emulsion, and disperse it by ultrasonication at 150W for 1h to form a composite coating liquid; take 100g of the first modified organosilicon micropowder and add it to the composite coating liquid, transfer it to a 55℃ constant temperature water bath, stir at 350r / min for 2h, and sonicate it for 10min every 30min during the process; after the reaction, centrifuge and separate it, wash it 3 times with deionized water, and dry it at 95℃ for 6h to obtain the second modified organosilicon micropowder; A3. Take 6g of 15nm nano-silica and 1.5g of polyethylene glycol 6000 and add them to 70ml of anhydrous ethanol. Disperse the mixture by ultrasonication at 150W for 1h. Then add 2g of styrene-butadiene rubber powder and 0.3g of dicumyl peroxide and stir until a uniform suspension is formed. Take 100g of the second modified organosilicon powder and add it to the suspension. Stir the mixture at 300r / min for 2.5h at 65℃ under nitrogen protection. After cooling to room temperature, centrifuge, wash twice with anhydrous ethanol, dry at 100℃ for 7h and pass through a 200-mesh sieve to obtain the modified organosilicon powder.
[0034] Example 5: Preparation of modified organosilicon micropowder. The specific preparation steps are as follows: A1. Take 100g of methylphenyl organosilicon micropowder with a particle size of 50μm, put it into a plasma treatment instrument, set the power to 120W, nitrogen atmosphere to 0.06MPa, and treat for 25min; mix 35ml of silane coupling agent KH-570, 110ml of anhydrous ethanol and 10ml of deionized water, adjust the pH to 5 with dilute acetic acid, add 0.3g of stearic acid and stir to dissolve, to prepare a modified solution, transfer it to a mixing vessel, and purge with nitrogen for 30min to remove oxygen; add the plasma-activated organosilicon micropowder to the mixing vessel, stir and react at 55℃ and 550r / min for 3.5h, during which nitrogen is purged for 10min every 1h to isolate oxygen; after the reaction is completed, filter, wash twice with anhydrous ethanol and once with deionized water, and dry at 95℃ for 5h to obtain the first modified organosilicon micropowder; A2. Take 15g of microcrystalline wax, heat and melt it, add 120ml of deionized water and 0.4g of sodium dodecyl sulfate, and emulsify it at 7000r / min for 30min under the condition of keeping it in a 55℃ water bath to obtain a microcrystalline wax emulsion; add 4g of polyether modified silicone oil to the emulsion, and disperse it by ultrasonication at 150W for 1h to form a composite coating liquid; take 100g of the first modified organosilicon micropowder and add it to the composite coating liquid, transfer it to a 55℃ constant temperature water bath, stir at 450r / min for 2.5h, and sonicate it for 10min every 30min during the process; after the reaction, centrifuge and separate it, wash it 3 times with deionized water, and dry it at 100℃ for 6h to obtain the second modified organosilicon micropowder; A3. Take 10g of 15nm nano-silica and 2.5g of polyethylene glycol 6000 and add them to 90ml of anhydrous ethanol. Disperse the mixture by ultrasonication at 150W for 1h. Then add 3.5g of styrene-butadiene rubber powder and 0.5g of dicumyl peroxide and stir until a uniform suspension system is formed. Take 100g of the second modified organosilicon micro powder and add it to the suspension system. Stir the mixture at 400r / min for 3.5h at 75℃ under nitrogen protection. After cooling to room temperature, centrifuge, wash twice with anhydrous ethanol, dry at 110℃ for 7h and pass through a 200-mesh sieve to obtain the modified organosilicon micro powder.
[0035] Example 6: Preparation of modified ultra-high molecular weight polyethylene powder. The specific preparation steps are as follows: B1. Take 100g of ultra-high molecular weight polyethylene powder, 2.5g of dicumyl peroxide, and 0.1g of antioxidant DSTDP, blend them, and add them to a twin-screw extruder. The barrel temperature gradient is: zone 1 150℃, zone 2 165℃, zone 3 170℃, and die head 168℃. The screw speed is 250r / min, and the feeding speed is 8kg / h. The extruded strip is cooled to room temperature with water and pulverized into powder with a particle size of 60μm. Take 100g of pretreated powder and add it to a mixer. Set the temperature to 135℃ and the speed to 60r / min. After the material softens, add 6.5g of maleic anhydride monomer and 0.3g of benzoyl peroxide. Continue the mixer reaction for 2h. During the reaction, increase the speed to 100r / min for 1min every 20min. After the reaction is completed, take out the material, cool it to room temperature, pulverize it, and extract it with acetone Soxhlet for 8h. The extracted material is dried at 80℃ for 5h to obtain the first modified ultra-high molecular weight polyethylene powder. B2. Take 10g of nano zinc oxide, 2g of polyethylene glycol 4000, and 0.1g of sodium dodecylbenzenesulfonate and add them to 100ml of deionized water. Disperse the mixture by ultrasonication at 150W for 1h. Add 0.4g of baking soda and 0.1g of citric acid to the dispersion and stir for 10min. Add 100g of the first-modified ultra-high molecular weight polyethylene powder to the dispersion and transfer it to a 50℃ constant temperature water bath. Stir at 400r / min for 2h, and sonicate for 10min every 30min. Add 5ml of silane coupling agent KH-550 and adjust the pH to 5.5 with dilute hydrochloric acid. Continue stirring for 1.5h. After the reaction is complete, filter to separate the material, wash it 3 times with deionized water, and dry it at 100℃ for 6h to obtain the second-modified ultra-high molecular weight polyethylene powder. B3. Take 100g of the second modified ultra-high molecular weight polyethylene powder and add it to a three-necked flask containing 150ml of toluene. Purge with nitrogen at a flow rate of 50ml / min for 30min, heat to 80℃, and stir at 300r / min for 30min. Add 10g of recovered liquid silica gel and 8g of polyurethane prepolymer, stir for 10min, and then add 0.2g of dibutyltin dilaurate. Stir and react for 3h under nitrogen protection. Add 5g of ethanolamine and continue the reaction for 1h. After the reaction is completed, cool to room temperature, centrifuge the material, wash the precipitate twice with toluene and once with anhydrous ethanol, and dry at 110℃ for 7h to obtain modified ultra-high molecular weight polyethylene powder.
[0036] Example 7: Preparation of modified ultra-high molecular weight polyethylene powder. The specific preparation steps are as follows: B1. Take 100g of ultra-high molecular weight polyethylene powder, 3.5g of dicumyl peroxide, and 0.2g of antioxidant DSTDP, blend them, and add them to a twin-screw extruder. The barrel temperature gradient is: zone 1 150℃, zone 2 165℃, zone 3 170℃, and die head 168℃. The screw speed is 250r / min, and the feeding speed is 8kg / h. The extruded strip is cooled to room temperature with water and pulverized into powder with a particle size of 60μm. Take 100g of pretreated powder and add it to a mixer. Set the temperature to 135℃ and the speed to 60r / min. After the material softens, add 7.5g of maleic anhydride monomer and 0.4g of benzoyl peroxide. Continue the mixer reaction for 2h. During the reaction, increase the speed to 100r / min for 1min every 20min. After the reaction is completed, take out the material, cool it to room temperature, pulverize it, and extract it with acetone Soxhlet for 8h. The extracted material is dried at 80℃ for 5h to obtain the first modified ultra-high molecular weight polyethylene powder. B2. Take 10g of nano zinc oxide, 2g of polyethylene glycol 4000, and 0.1g of sodium dodecylbenzenesulfonate and add them to 100ml of deionized water. Disperse the mixture by ultrasonication at 150W for 1h. Add 0.6g of baking soda and 0.2g of citric acid to the dispersion and stir for 10min. Add 100g of the first-modified ultra-high molecular weight polyethylene powder to the dispersion and transfer it to a 50℃ constant temperature water bath. Stir at 400r / min for 2h, and sonicate for 10min every 30min. Add 7ml of silane coupling agent KH-550 and adjust the pH to 5.5 with dilute hydrochloric acid. Continue stirring for 1.5h. After the reaction is complete, filter and separate the material. Wash it three times with deionized water and dry it at 100℃ for 6h to obtain the second-modified ultra-high molecular weight polyethylene powder. B3. Take 100g of the second modified ultra-high molecular weight polyethylene powder and add it to a three-necked flask containing 150ml of toluene. Purge with nitrogen at a flow rate of 50ml / min for 30min, heat to 80℃, and stir at 300r / min for 30min. Add 12g of recovered liquid silica gel and 10g of polyurethane prepolymer, stir for 10min, and then add 0.4g of dibutyltin dilaurate. Stir and react for 3h under nitrogen protection. Add 6g of ethanolamine and continue the reaction for 1h. After the reaction is completed, cool to room temperature, centrifuge the material, wash the precipitate twice with toluene and once with anhydrous ethanol, and dry at 110℃ for 7h to obtain modified ultra-high molecular weight polyethylene powder.
[0037] Comparative Example 1: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the modified organosilicon micropowder prepared in Example 4 and used in Example 3 are replaced with unmodified organosilicon micropowder to prepare anti-fouling PCR ABS laser engraving material.
[0038] Comparative Example 2: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the modified ultra-high molecular weight polyethylene powder prepared in Example 7 used in Example 3 is replaced with unmodified ultra-high molecular weight polyethylene powder to prepare anti-fouling PCR ABS laser engraving material.
[0039] Comparative Example 3: Preparation of anti-fouling PCR ABS laser-engraved material. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the modified organosilicon micropowder prepared in Example 4 used in Example 3 is replaced with unmodified organosilicon micropowder, and the modified ultra-high molecular weight polyethylene powder prepared in Example 7 is replaced with unmodified ultra-high molecular weight polyethylene powder, so as to prepare a stain-resistant PCR ABS laser engraving material. Performance testing
[0040] 1. Add the laser engraving material to the injection molding machine and mold it at 250℃ to create a test sample with a design size of 20mm x 80mm and a thickness of 2mm. Place the test sample under the laser engraving machine, adjust the appropriate laser engraving machine parameters, and engrave complete and clear white characters.
[0041] 2. Use an injection molding machine to mold the laser engraving material into computer keypads at 250°C, and then use a laser engraving machine to engrave complete and clear white characters on the keypads.
[0042] To verify the comprehensive performance of the stain-resistant PCR ABS laser engraving material, the laser engraving material of this invention (Examples 1-3) and ordinary laser engraving materials (Comparative Examples 1-3) were used as test objects. Test samples of 20mm×80mm and 2mm thickness and finished computer keypads were prepared by injection molding. Systematic tests were carried out focusing on the clarity of characters (simulating daily pollution scenarios) and the service life of the keypad. The specific results are as follows: Test sample test
[0043] Button finished product testing
[0044] The clarity level in the table is graded by the number of "+" signs, with "++++++" being the best (sharp characters without blurring or stains), "+" being poor (blurred but still legible characters), and "-" being the worst (severely blackened and unrecognizable characters).
[0045] In the character clarity test, Examples 1-3 demonstrated excellent stain resistance and consistency with laser engraving effects: after soaking in synthetic sweat for 5 minutes and alcohol for 5 minutes, the characters in all three examples remained sharp and clear, with no obvious stain residue. Example 3 achieved the best rating of "++++++". Even with highly adhesive contaminants such as lipstick and carbonated drinks, Examples 1-3 maintained clear character outlines without contaminant penetration or residue. In contrast, the comparative examples 1-2, which replaced a single unmodified powder, showed a decrease in character clarity under sweat and alcohol conditions, with characters becoming blurred or partially blackened after lipstick and carbonated drink contamination. Comparative example 3, which used two unmodified powders, showed severely blackened and illegible characters (rating "-") under strong contamination conditions, highlighting the crucial supporting role of modified powder in the material's stain resistance and laser engraving effect.
[0046] In the life test of the finished computer keypad (after 20 million presses), the characters in Examples 1-3 remained stable, and Examples 2-3 maintained a rating of "+++++" or higher, with no character wear or blurring. The characters in Comparative Examples 1-2 showed obvious wear, and in Comparative Example 3, due to the poor compatibility between the unmodified powder and PCR ABS resin, the keypad characters completely lost their legibility.
[0047] Overall test results show that this invention effectively solves the problems of poor stain resistance and unstable laser engraving effect of traditional PCR ABS recycled materials by synergistic modification of modified organosilicon micro powder and modified ultra-high molecular weight polyethylene powder, and optimization of the compounding of azodicarbonamide and compatibilizer. The stain-resistant PCR ABS laser engraving material prepared by this invention has outstanding performance in terms of daily pollution resistance and long-term use stability, and can meet the application needs of keyboard keys and other scenarios with high requirements for functionality and durability.
[0048] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. Anti-fouling PCR ABS laser engraved material, characterized in that: The modified organic silica powder is prepared by the following steps: A1, taking methylphenyl organic silica powder with a particle size of 50 microns, placing it into a plasma treatment instrument, setting the power to 120 W, the nitrogen atmosphere to 0.06 MPa, and treating it for 18-25 min; mixing silane coupling agent KH-570, anhydrous ethanol, and deionized water in a certain proportion, adjusting the pH to 5 with dilute acetic acid, adding stearic acid to stir and dissolve, preparing a modified liquid, transferring it into a mixing kettle, and purging nitrogen for 30 min to remove oxygen; adding the plasma-activated organic silica powder into the mixing kettle, stirring at 45-55 DEG C and a speed of 550 r / min for 2.5-3.5 h, purging nitrogen for 10 min every 1 h to isolate oxygen during the reaction; after the reaction, filtering, washing twice with anhydrous ethanol and once with deionized water, and drying at 85-95 DEG C for 5 h, the first modified organic silica powder is obtained; A2, taking microcrystalline wax, heating and melting, adding deionized water and sodium dodecyl sulfate, emulsifying at 55 DEG C under water bath conditions at a high speed of 6000-7000 r / min for 30 min to prepare a microcrystalline wax emulsion; adding polyether modified silicone oil into the emulsion, and ultrasonic dispersing for 1 h to form a composite coating liquid; taking the first modified organic silica powder, adding it into the composite coating liquid, transferring it into a constant temperature water bath at 55 DEG C, and stirring at 350-450 r / min for 2-2.5 h, ultrasonic dispersing for 10 min every 30 min during the reaction; after the reaction, centrifuging, washing with deionized water for 3 times, and drying at 95-100 DEG C for 6 h, the second modified organic silica powder is obtained; A3, taking nano-silicon dioxide with a particle size of 15 nm and polyethylene glycol 6000, adding them into anhydrous ethanol, and ultrasonic dispersing for 1 h; then adding butadiene-styrene rubber powder and dicumyl peroxide, and stirring until a uniform suspension system is formed; taking the second modified organic silica powder, adding it into the suspension system, stirring at 300-400 r / min under nitrogen protection at 65-75 DEG C for 2.5-3.5 h; after cooling to room temperature, centrifuging, washing with anhydrous ethanol for 2 times, drying at 100-110 DEG C for 7 h, and passing through a 200-mesh screen, the modified organic silica powder is obtained.
2. The anti-fouling PCR ABS laser-engraved material according to claim 1, characterized in that: The modified super high molecular weight polyethylene powder is prepared by the following steps: 3. The anti-staining PCR ABS laser engraved material according to claim 1, characterized in that: B1, take the ultra-high molecular weight polyethylene powder, dicumyl peroxide, antioxidant DSTDP blend into a twin-screw extruder, the temperature gradient of the barrel: 150 DEG C in the first area, 165 DEG C in the second area, 170 DEG C in the third area, 168 DEG C in the head, screw speed 250 r / min, feeding speed 8 kg / h, the extruded strip is cooled to room temperature by water, and is crushed into a powder with a particle size of 60 μm; take the pretreated powder into an internal mixer, set the temperature to 135 DEG C and the speed to 60 r / min, after the material softens, add maleic anhydride monomer and benzoyl peroxide, continue the internal mixing reaction for 2 h, during which the speed is increased to 100 r / min every 20 min for 1 min; after the reaction is completed, the material is cooled to room temperature, crushed, Soxhlet extracted with acetone for 8 h, and the extracted material is dried at 80 DEG C for 5 h to obtain the first modified ultra-high molecular weight polyethylene powder; B2, take the nano zinc oxide, polyethylene glycol 4000, and sodium dodecyl benzene sulfonate into deionized water, and ultrasonically disperse for 1 h at 150 W; add baking soda and citric acid to the dispersion liquid and stir for 10 min; take the first modified ultra-high molecular weight polyethylene powder into the dispersion liquid, transfer into a 50 DEG C constant temperature water bath, and stir at 400 r / min for 2 h, ultrasonic for 10 min every 30 min; further add silane coupling agent KH-550, adjust the pH to 5.5 with dilute hydrochloric acid, and continue to stir for 1.5 h; after the reaction is completed, filter and separate the material, wash with deionized water for 3 times, and dry at 100 DEG C for 6 h to obtain the second modified ultra-high molecular weight polyethylene powder; B3, take the second modified ultra-high molecular weight polyethylene powder into a three-necked flask containing toluene, pass nitrogen at a flow rate of 50 ml / min for 30 min, heat to 80 DEG C, and stir at a speed of 300 r / min for 30 min; add recycled liquid silica gel and polyurethane prepolymer, stir for 10 min, then add dibutyltin dilaurate, and stir for 3 h under nitrogen protection; add ethanolamine, and continue to react for 1 h; after the reaction is completed, cool to room temperature, centrifugally separate the material, wash the precipitate with toluene for 2 times and with anhydrous ethanol for 1 time, and dry at 110 DEG C for 7 h to obtain the modified ultra-high molecular weight polyethylene powder.
4. The anti-fouling PCR ABS laser-engraved material according to claim 3, characterized in that: The recycled liquid silica gel used in the modified ultra-high molecular weight polyethylene powder is unvulcanized transparent silica gel, and is pretreated by the following operation: after being crushed through a 100-mesh filter screen to remove impurities, the recycled liquid silica gel is put into a vacuum degassing machine, degassed at 120 DEG C and-0.095 MPa for 2 h.
5. The anti-fouling PCR ABS laser-engraved material of claim 2, wherein: The amount ratio of methylphenyl silicone powder, silane coupling agent KH-570, anhydrous ethanol, deionized water, and stearic acid in A1 is 100 g: 25-35 ml: 90-110 ml: 6-10 ml: 0.2-0.3 g; The amount ratio of microcrystalline wax, deionized water, sodium dodecyl sulfate, polyether modified silicone oil, and first modified silicone powder in A2 is 10-15 g: 90-120 ml: 0.2-0.4 g: 2-4 g: 100 g; The dosage ratio of nano-silicon dioxide, polyethylene glycol 6000, anhydrous ethanol, butadiene rubber powder, dicumyl peroxide, and the second modified silicone powder in A3 is 6-10 g: 1.5-2.5 g: 70-90 ml: 2-3.5 g: 0.3-0.5 g: 100 g.
6. The anti-fouling PCR ABS laser-engraved material of claim 3, wherein: The dosage ratio of ultra-high molecular weight polyethylene powder, dicumyl peroxide, and antioxidant DSTDP in B1 is 100 g: 2.5-3.5 g: 0.1-0.2 g; the dosage ratio of pretreated powder, maleic anhydride monomer, and benzoyl peroxide is 100 g: 6.5-7.5 g: 0.3-0.4 g; The dosage ratio of nano-zinc oxide, polyethylene glycol 4000, sodium dodecylbenzenesulfonate, deionized water, baking soda, citric acid, the first modified ultra-high molecular weight polyethylene powder, and silane coupling agent KH-550 in B2 is 10 g: 2 g: 0.1 g: 100 ml: 0.4-0.6 g: 0.1-0.2 g: 100 g: 5-7 ml; The dosage ratio of the second modified ultra-high molecular weight polyethylene powder, toluene, recovered liquid silicone, polyurethane prepolymer, dibutyltin dilaurate, and ethanolamine in B3 is 100 g: 150 ml: 10-12 g: 8-10 g: 0.2-0.4 g: 5-6 g; the polyurethane prepolymer is aromatic type with an NCO content of 6.5% and a number average molecular weight of 1000-1500.
7. The anti-fouling PCR ABS laser-engraved material of claim 2, wherein: The modified silicone powder is synergistically improved in stain resistance and compatibility through three modifications. The first modification uses plasma treatment combined with silane coupling agent KH-570 and stearic acid complex modification liquid to modify, activate the surface active sites of the powder, and graft polar groups to improve the interfacial bonding force with PCRABS resin; The second modification uses microcrystalline wax-polyether modified silicone oil to complex coat, builds a low surface energy hydrophobic layer, and gives the powder basic stain resistance; The third modification uses nano-silicon dioxide and butadiene rubber powder to graft coat, forms a micro-nano rough structure, builds a micro-nano rough hydrophobic structure to strengthen the hydrophobic stain resistance, and enhances the wear resistance and self-lubricating properties of the powder, optimizing the overall stain resistance and laser engraving adaptability of the material.
8. The anti-fouling PCR ABS laser-engraved material of claim 3, wherein: In the three modification processes of the modified ultra-high molecular weight polyethylene powder, the first modification introduces polar groups through maleic anhydride grafting reaction, the second modification uses nano-zinc oxide to adsorb and deposit on the surface of the powder through electrostatic interaction and hydrogen bonding, forming a micro-nano rough structure, and synergistically realizing hydrophobic stain resistance with low surface energy components, and the third modification uses recovered liquid silicone and polyurethane prepolymer to complex coat, building a surface structure with both lubricity and stain resistance.
9. A method for preparing an anti-fouling PCR ABS laser engraved material, characterized by: Specifically comprising the following steps: S1, put all solid raw materials into a vacuum drying oven, set the temperature to 85℃ and the vacuum degree to -0.09MPa, and dry for 6h; take 0.1-0.5 parts of carbon black, add 0.05-0.1 parts of polyethylene wax and 0.4-1 parts of anhydrous ethanol, put into a small grinding machine, grind and disperse to break the carbon black agglomerates, make the particle size distribution D90≤5μm, and prepare a uniform pigment paste; S2, 0.5-2.5 parts of glass beads, 0.5-2 parts of anatase titanium dioxide, 6-10 parts of modified silicone powder are added into the high-speed homogenizing tank, the rotation speed is set to 500 r / min, stirring at room temperature for 5 min, then 0.2-1 parts of silane coupling agent KH-550 is sprayed, and stirring is continued for 10 min; the rotation speed is reduced to 300 r / min, 50-90 parts of PCR ABS resin and 2-15 parts of modified ultra-high molecular weight polyethylene powder are added, after all the materials are added, the rotation speed is slowly increased to 800 r / min, and stirring is carried out for 15 min; S3, keep the rotation speed and add 2-8 parts of azodicarbonamide, 2-6 parts of methyl methacrylate-butyl acrylate copolymer, 1-3 parts of antioxidant 1010 and 0.5-1.0 parts of calcium-zinc stabilizer in turn, interval 3 min for each material, stirring 25 min, no visible agglomeration; the prepared pigment paste is uniformly sprayed into the mixed material, the stirring speed is set to 800 r / min, 200W, 20kHz ultrasonic dispersion is carried out at the same time, 5 min ultrasonic dispersion every 15 min, and the stirring is continued for 80 min; S4, the mixed material is sent into a double screw extruder, the temperature is set to 175℃ for feeding section, 195℃ for compression section, 202℃ for melting section and 208℃ for die head section, the screw rotation speed is 350 rpm, and the feeding speed is 22 kg / h; the strip is slowly cooled in a 45℃ water tank, shaped in a 20℃ water tank, and then pelletized to obtain anti-fouling type PCR ABS laser engraving master batch.